PENGAMBILAN KEPUTUSAN KONSUMEN DALAM BERBELANJA BAHAN PANGAN - Steven A. Rumbayan; Esry O. Laoh; Agnes E. Loho; Charles R. Ngangi (COCOS, 2016)
ABTRACTThe purpose of this research is knowing consumer decision making in foodstuff trade in Teling Community, Wanea District, Manado City and as additional benefit of knowledge and information about consumer decision making foodstuffs trade. This study used primary data and secondary data. The sourced of primary data obtained from interviews with respondent by questionnaire, secondary data taken from Teling district office, Wanea District, Manado City. The Sampling taken by purposive sampling, 45 respondent and analyzed using qualitative descriptive. The research result showed that foodstuffs that always buy in the modern market were sugar, eggs, milk, chicken, beef, cooking oil and fruits, while in traditional market were rice and vegetables, then the most frequent visiting place was modern market with the number of respondents 27 people or 60%, while in traditional market as many as 18 people or 40%. The reason respondent to buy in modern market is : 1). Product quality in assured because the respondent perceive that quality of products in modern market better than traditional market. 2). Cleanliness, because the modern market has a janitor who always there. 3). Neatness, because the modern market already neatly packed for each product they wanted. 4). Using packaging, because the product using packaging make respondent feel the product to buy is clean. Whereas the reason respondent choosing to buy in traditional market is : 1). The cheaper price, because respondent viewed the priced in traditional market cheaper than modern market. 2). Fresher, the fact product in traditional market more fresher compared than modern market. 3). For who have enough money because the high income, respondent would choose a good product because better product get higher price.Keyword : Consumer decision making, Modern Market, Traditional Market,